Information aggregation in an entrepreneurship portal - Figueiredo, R.; Costa, C. J.; Aparicio, M. (Workshop on Open Source and Design of Communication, OSDOC 2012, 2012)
This study can be applied in multiple contexts. The main focus is to demonstrate the ability to gather information from multiple sources, using open source platforms and technologies for publishing information. In this paper, we purpose a conceptual model to an entrepreneurship portal based on a search engine paradigm. Here it is purposed model derived from the literature and validated using open source technology. In this study we propose an open source platform That aggregates information from Various sources, organizing the information needed. On this platform the main task is to gather information from Several sources, using publishing technologies. Described in this paper it multiple scenarios Applied to an entrepreneurship portal.